Policy responses to COVID-19 in Sri Lanka and the consideration of Indigenous Peoples. Issue 144 (June 2023) - Galappaththi, Eranga K.; Perera, Chrishma D.; Dharmasiri, Indunil P.; Ford, James D.; Kodithuwakku, Sarath S.; Chicmana-Zapata, Victoria; Zavaleta-Cortijo, Carol; Pickering, Kerrie; van Bavel, Bianca; Hyams, Keith; Arotoma-Rojas, Ingrid; Akugre, Francis Awaafo; et al.
Abstract: COVID-19 has had uneven impacts on health and well-being, with Indigenous communities in the Global South facing some of the highest risks. Focusing on the experience of Sri Lanka, this study identifies key policy responses to COVID-19, documents how they evolved over two years of the pandemic, and examines if and how government responses have addressed issues pertaining to Indigenous Peoples. Drawing upon an analysis of policy documents (n = 110) and interviews with policymakers (n = 20), we characterize seven key policy responses implemented by the Sri Lankan government: i) testing for and identifying COVID-19; ii) quarantine procedures; iii) provisional clinical treatments; iv) handling other diseases during COVID-19; v) movement; vi) guidelines to be adhered to by the general public; and vii) health and vaccination. The nature of these responses changed as the pandemic progressed. There is no evidence that policy development or implementation incorporated the voices and needs of Indigenous Peoples. Highlights: The study investigates COVID-19 government policy responses over two years in Sri Lankan Indigenous peoples (IPs) setting. The study introduces a novel approach to policy prioritization based on "relevance to IPs" and "evidence of implementation". Study prioritized seven policy responses to COVID-19, based on 110 policy documents and 20 policy interviews. No or very little, consideration was given to IPs in formulating policy responses in Sri Lanka.